The Importance of Cognitive Domains and the Returns to Schooling in South Africa: Evidence from Two Labor Surveys - Plamen Nikolov; Nusrat Abedin Jimi (Institute of Labor Economics (IZA), 2020)
Numerous studies have considered the important role of cognition in estimating the returns to schooling. How cognitive abilities affect schooling may have important policy implications, especially in developing countries during periods of increasing educational attainment. Using two longitudinal labor surveys that collect direct proxy measures of cognitive skills, we study the importance of specific cognitive domains for the returns to schooling in two samples. We instrument for schooling levels and we find that each additional year of schooling leads to an increase in earnings by approximately 18-20 percent. The estimated effect sizes—based on the two-stage least squares estimates—are above the corresponding ordinary least squares estimates. Furthermore, we estimate and demonstrate the importance of specific cognitive domains in the classical Mincer equation. We find that executive functioning skills (i.e., memory and orientation) are important drivers of earnings in the rural sample, whereas higher-order cognitive skills (i.e., numeracy) are more important for determining earnings in the urban sample. Although numeracy is tested in both samples, it is only a statistically significant predictor of earnings in the urban sample.
Keywords: I21; F63; F66; N37; 330; returns to schooling; cognitive skills; returns to cognition; developing countries; Sub-Saharan Africa